2021
DOI: 10.1158/1078-0432.ccr-21-2635
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant and Adjuvant Nivolumab and Lirilumab in Patients with Recurrent, Resectable Squamous Cell Carcinoma of the Head and Neck

Abstract: This open-label, single-arm, non-randomized, multicenter phase II trial using neoadjuvant nivolumab and lirilumab before and after salvage surgical resection is, to our knowledge, the first study to evaluate immune checkpoint blockade as a therapeutic strategy for locoregionally recurrent, surgically salvageable head and neck cancer. Our findings of substantial rates of pathologic response (43%), excellent safety and tolerability, and overall encouraging survival outcomes in heavily pre-treated patients with l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 40 publications
1
33
0
3
Order By: Relevance
“…The introduction of anti-PD-1 immunotherapy allowed long-term survival in a small proportion of patients [ 5 ]. Today, anti-PD-1 immunotherapy is shifting from the palliative setting to earlier disease stages up to neoadjuvant immunotherapy, which additionally increases the response rate [ 6 , 7 ]. However, more than half of patients do not respond even to modern neoadjuvant immunotherapy protocols.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of anti-PD-1 immunotherapy allowed long-term survival in a small proportion of patients [ 5 ]. Today, anti-PD-1 immunotherapy is shifting from the palliative setting to earlier disease stages up to neoadjuvant immunotherapy, which additionally increases the response rate [ 6 , 7 ]. However, more than half of patients do not respond even to modern neoadjuvant immunotherapy protocols.…”
Section: Introductionmentioning
confidence: 99%
“…The first monoclonal antibodies targeting NK cell IR and to be clinically tested were the anti-KIR2DL1, -KIR2DL2, and -KIR2DL3 molecule lirilumab, which blocks the inhibitory interaction of the KIR with HLA-C proteins [ 89 ], and the anti-NKG2A antibody monalizumab, interfering with the binding of the IR NKG2A, expressed by subsets of NK cells and CD8+ T lymphocytes, with its ligand HLA-E [ 90 , 91 ]. The former was recently tested in clinical trials in combination with the anti-PD-1 antibody nivolumab against hematologic [ 92 ] and solid (head and neck) tumors [ 93 ] and showed some efficiency, even in terms of disease free and overall survival [ 93 ]. Regarding monalizumab, a phase II trial revealed, in combination with the anti-epithelial growth factor receptor (EGFR) antibody cetuximab, an objective response rate of 31% in pretreated head and neck squamous cell carcinoma with tolerable side effects [ 90 ].…”
Section: Harnessing Of Autologous Nk Cellsmentioning
confidence: 99%
“…[20 ▪ ] and Hanna et al . [21 ▪ ]), with a targeted therapeutic (Merlino et al . [11 ▪▪ ,12 ▪▪ ]), or with primary tumour stereotactic body radiation therapy (SBRT) (Leidner et al [15 ▪▪ ]) are summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…and Hanna et al . [21 ▪ ]). One assessed change in tumour physical measurement from the clinical, pretreatment measurements using callipers (Knochelmann et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation